Sacrificial template formation of CoMoO₄ hollow nanostructures constructed by ultrathin nanosheets for robust lithium storage - Wang, Yansen; Sun, Yanfang; Zhang, Xiao; Wen, Yong-hong; Guo, Jinxue (RSC advances, 2016)
Hierarchical hollow structures composed of two-dimensional nanostructures are desirable and challenging research subjects in the synthesis and application of nanomaterials. In the present work, CoMoO₄ hollow nanostructures assembled by nanosheet subunits were successfully prepared via a facile solvothermal method using SiO₂ nanospheres as the sacrificial template. In the synthesis process, the formation and assembly of CoMoO₄ nanosheets, as well as the template removal, were carried out simultaneously, thus avoiding the cumbersome multi-step process of the traditional template method. The obtained nanosheets-constructed hollow nanostructures possess combined structural advantages for robust electrochemical properties as anode materials for lithium-ion batteries, such as a porous and robust framework, high surface area for electrode/electrolyte contact, reduced lithium diffusion path, and a hollow interior to accommodate the volume variation associated with the electrochemical cycles. Hence, the CoMoO₄ electrode was able to deliver good lithium storage properties, including high specific capacity (1066 mA h g⁻¹ at a current density of 500 mA g⁻¹ after 200 cycles), good cyclic stability, and an especially excellent rate performance.